Neuromuscular fatigue during repeated maximal static exertion in international rugby union player - Lacome, M.; Piscione, J.; Bourdin, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Rugby is an intermittent high intensity activity, which differs in nature with player position. Forwards are mainly involved in static exertion whereas backwards performed more sprints. Physiological and metabolic responses of repeated-sprint activities specific to field-based time sports had previously been well documented (e.g. (1)) but studies dealing with physiological consequences of repeated isometric activity were scarce. The aim of this study was to explore neuromuscular fatigue occurrence during repeated isometric maximal exercise simulating scrum effort. Methods: The experiments were carried out on 9 French male international rugby union players (18.8 ± 0.4 years, 186 ± 5.5 cm, 100.8 ± 11.2 kg). Subjects were asked to perform, as hard as they can, twelve 5-s isometric static exertions against a scrum simulator (FFR-Thales Scrum Simulator) interspaced with 15-s rest. Strong verbal encouragement was provided to each subject during the entire testing procedure. During the test, all the forces expressed against the scrum simulator were record with 3 forces sensors MC5-10000 (AMTI inc, Waterdown, MA). EMG signal was treated using Root Mean Square (RMS) and Mean Power Frequency (MPF) methods for rectus femoris (RF), vastus medialis (VM) and vastus lateralis (VL). EMG RMS and MPF were normalized with respect to the value obtained for the first repetition. All data were synchronized using a Biopac MP150 (Biopac System inc, CA, USA). Results: Preliminary results demonstrated that mean force decreased significantly (p<0.05) from the fourth repetition (1966.5 ± 336.4 N) to the last one (1819.2 ± 454.8 N). Normalized RMS of the VM was significantly lower from the fourth repetition (p<0.05). For RF and VL, normalized MPF decreased significantly from the fourth repetition (96.0 ± 4.2 and 95.7 ± 3.8 % respectively; p<0.05) but not for VM. Discussion: In line with previous study about repeated sprint exercise (2), our preliminary results showed decline in performance during repeated maximal isometric exercise matched with neuromuscular fatigue. Decrease in RMS values for VM could be interpreted as change in coordination. Decrease in MPF values for VL and RF tended to demonstrate that peripheral fatigue occurs. It is interesting to note that decrease in force was less than these observed in repeated maximal running or cycling (2) for similar exhausting conditions.